DEFINITION OF PERFORMANCE CRITERIA FOR BIOLOGICAL ACTION OF OPTICAL RADIATION ON THE LIVING ORGANISM - Chervinsky, L; Radko І. (Енергетика і автоматика, 2016)
Theoretically grounded thebmathematical expressions to determine the effective dose of ultraviolet radiation of farm animals, particularly taking into account the breed of animals, their weight differences, the health, the optical properties of the outer cover, and especially conditions.